2013
DOI: 10.5055/ajdm.2013.0124
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of involuntary exposure to benzene following a flaring incident at British Petroleum refinery in Texas City

Abstract: This retrospective pilot study found that environmental benzene exposure from the BP's flaring incident appears to pose significant health risks including specific alteration of blood cells and liver enzymes, indicating that subjects exposed to benzene may be at a higher risk of developing hepatic or blood related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…On the other hand, the toxicity of organic solvents and aromatic hydrocarbons (toluene, ethylbenzene, xylenes) has been widely recognized in the literature [13]. Aromatic hydrocarbons affect lymphatic, hematopoietic, hepatic, renal and nervous systems [14,15]. In addition, they cause acute effects on skin and mucous membranes [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the toxicity of organic solvents and aromatic hydrocarbons (toluene, ethylbenzene, xylenes) has been widely recognized in the literature [13]. Aromatic hydrocarbons affect lymphatic, hematopoietic, hepatic, renal and nervous systems [14,15]. In addition, they cause acute effects on skin and mucous membranes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although benzene-exposed male subjects had significantly higher mean serum AST levels (IU/l) as compared with unexposed male subjects (33.3±6.2 vs. 21.9±5.5, p = 0.0158), no significant differences were observed between benzene-exposed and unexposed female subjects (21.1±5.2 vs. 18.6±4.9, p = 0.129). Similarly, benzene-exposed male subjects had significantly higher mean serum ALT levels (IU/l) as compared with unexposed male subjects (37±7.8 vs. 27.8±4.6, p = 0.023), no significant differences were observed between benzene-exposed the BP's prolonged flaring incident [23]. More specifically, in this study, we evaluated and compared the hematological and hepatic functions among benzene-exposed smoking subjects vs. unexposed smoking subjects.…”
Section: Resultsmentioning
confidence: 91%
“…To assess the potential health consequences of this ambient benzene exposure that resulted from the BP flaring incident, a series of studies are being conducted examining the hematological and hepatic functions in affected subjects. The initial findings of these studies have revealed that benzene exposure has significantly altered the hematological and hepatic indices in the case of the exposed subjects as compared with the unexposed subjects [23][24][25][26][27]. In addition, those persons exposed to benzene had a range of illness symptoms and an altered profile of urinary phenol indicating their vulnerability to increased health complications [28].…”
Section: Ijomeh 2017;30(6)mentioning
confidence: 99%
See 2 more Smart Citations